2019
DOI: 10.4314/ijbcs.v12i6.1
|View full text |Cite
|
Sign up to set email alerts
|

Post-treatment assessment of praziquantel efficacy among school-age children infected with schistosomiasis in Ipogun area of Ondo State, Nigeria

Abstract: Schistosomiasis, a major public health challenge is caused by trematodes of the genus Schistosoma whose intermediate host is snails. Sub-Saharan African (SSA) carried 85% of the global burden of this infection principally amongst school age children. Similarly, Nigeria bears the highest weight of this highly preventable infection in SSA. Preventive chemotherapy (PC) with 40-60 mg\kg praziquantel (PZQ) annually is the focal control strategy in endemic areas. Despite more than two decades of PZQ usage in Nigeria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…The relationship between sex and risk of infection is therefore equivocal and varies with the cultural background of the people [ 19 , 27 , 30 ]. The relationship may vary from one region of the country to another and from one transmission season to another, even within the same endemic communities [ 42 ]. Whatever may be the case, it is often partly explained by differences in the social and occupational roles taken up by each participant that could affect water-related contact, including frequency, duration, and level of submergence, which may be influenced by age and cultural beliefs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between sex and risk of infection is therefore equivocal and varies with the cultural background of the people [ 19 , 27 , 30 ]. The relationship may vary from one region of the country to another and from one transmission season to another, even within the same endemic communities [ 42 ]. Whatever may be the case, it is often partly explained by differences in the social and occupational roles taken up by each participant that could affect water-related contact, including frequency, duration, and level of submergence, which may be influenced by age and cultural beliefs [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between sex and risk of infection is therefore equivocal and varies with the cultural background of the people [19,27,30]. The relationship may vary from one region of the country to another and from one transmission season to another, even within the same endemic communities [42].…”
Section: Discussionmentioning
confidence: 99%
“…Schistosomiasis is endemic in Sub-Saharan Africa (SSA), where it mainly affects the poor and the underprivileged (3,13,14). The disease has significant economic and public health implications in developing countries where it mostly affects populations, particularly in rural and some peri urban areas.…”
Section: Introductionmentioning
confidence: 99%
“…Schistosomiasis is a chronic disease also well known as bilharzia or snail fever, parasitic flukes of the genus Schistosoma cause it. It remains extremely prevalent in many low-income and middle-income countries (Steinauer et al, 2008;Colley et al, 2014;Adenowo et al, 2015: Oboh et al, 2018Li et al, 2019). The estimated global prevalence showed that at least 229 million people required preventive treatment in 2018 and more than 97.2 million people were reported to have been treated (GBD, 2016;WHO, 2017WHO, , 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Schistosoma intercalatum affects the GI tract but are associated with a lower morbidity. Schistosoma matheei and Schistosoma bovis are occasional parasites of human and Schistosoma incognitum may also show infective strains to humans (Corachan, 2002;Oboh et al, 2018). The species differ in their final location in the human host, the species of the intermediate host(snail), the pathology they induce, and the number, size and shape of the eggs produced (IARC, 2012).…”
Section: Introductionmentioning
confidence: 99%